2015
DOI: 10.1111/1752-1688.12327
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Trends of Nutrients and Sediment from the Nontidal Chesapeake Watershed: An Assessment of Progress by River and Season

Abstract: To assess historical loads of nitrogen (N), phosphorus (P), and suspended sediment (SS) from the nontidal Chesapeake Bay watershed (NTCBW), we analyzed decadal seasonal trends of flow-normalized loads at the fall-line of nine major rivers that account for >90% of NTCBW flow. Evaluations of loads by season revealed N, P, and SS load magnitudes have been highest in January-March and lowest in July-September, but the temporal trends have followed similar decadal-scale patterns in all seasons, with notable excepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 61 publications
6
65
0
Order By: Relevance
“…The mean parameter µ varies between 9.5 and 19.6 for TN and between 13.4 and 24.4 for TP in the Chesapeake monitoring network, corresponding to t average of 10.5-20.6 days for TN and 14.4-25.4 days for TP, respectively. This is consistent with the fact that these sites have typically been sampled roughly once or twice monthly, along with additional sampling during storm flows (Langland et al, 2012;Zhang et al, 2015).…”
Section: Empirical and Theoretical Cdfssupporting
confidence: 77%
See 1 more Smart Citation
“…The mean parameter µ varies between 9.5 and 19.6 for TN and between 13.4 and 24.4 for TP in the Chesapeake monitoring network, corresponding to t average of 10.5-20.6 days for TN and 14.4-25.4 days for TP, respectively. This is consistent with the fact that these sites have typically been sampled roughly once or twice monthly, along with additional sampling during storm flows (Langland et al, 2012;Zhang et al, 2015).…”
Section: Empirical and Theoretical Cdfssupporting
confidence: 77%
“…One such network is the Chesapeake Bay River Input Monitoring Program, which typically samples streams roughly once or twice monthly, accompanied with additional sampling during storm flows (Langland et al, 2012;Zhang et al, 2015). These data were obtained from the US Geological Survey National Water Information System (http://doi.org/ 10.5066/F7P55KJN).…”
Section: Examination Of Sampling Irregularity In Real Rivermentioning
confidence: 99%
“…These trends correspond to changes in the net biogeochemical production and net transport of NH 4 + and NO 2+3 − that operate over seasonal and regional scales in Chesapeake Bay and other comparable estuaries (Cloern and Jassby ). The reductions in NH 4 + and increases in dissolved O 2 also correspond to recent, but modest declines in nitrogen input from the Susquehanna River (Murphy et al ; Zhang et al ; Harding et al b ; Testa et al ).…”
Section: Resultsmentioning
confidence: 81%
“…And although our case study data set does not contain any censored values-i.e., concentrations reported as less than detection limit (typically 0.5 mg/L for SS)-there are published approaches for handling such data [e.g., Tobin, 1958], and others have shown how WRTDS can be implemented in such cases [Chanat et al, 2016;Moyer et al, 2012;Zhang et al, 2015]. In fact, WRTDS has already been adopted by many investigators to estimate concentration and flux for a variety of constituents, including nitrogen, phosphorus, chloride, and dissolved organic carbon.…”
Section: Methods Application: Case Study and Broader Relevancementioning
confidence: 99%
“…The validity of such relationships is confounded, however, by other factors that affect concentrations in natural rivers. This site lies downstream of Conowingo Reservoir, where prior studies have suggested long-term decline in the reservoir's ability to trap sediment before it reaches Chesapeake Bay [Hirsch, 2012;The Lower Susquehanna River Watershed Assessment Team, 2015;Zhang et al, 2013Zhang et al, , 2015Zhang et al, , 2016b. This site lies downstream of Conowingo Reservoir, where prior studies have suggested long-term decline in the reservoir's ability to trap sediment before it reaches Chesapeake Bay [Hirsch, 2012;The Lower Susquehanna River Watershed Assessment Team, 2015;Zhang et al, 2013Zhang et al, , 2015Zhang et al, , 2016b.…”
Section: Complexities With C-q Interpretationmentioning
confidence: 99%